Inhibition of Dimethylarginine Dimethylaminohydrolase 1 Improves the Outcome of Sepsis in Pregnant Mice. Issue 4 (October 2020) - Zölner, Julia; Lambden, Simon; Nasri, Noor Mohd; Johnson, Mark R.; Leiper, James
Abstract : ABSTRACT: Sepsis is one of the most important causes of maternal mortality. In our previous work, we established a polymicrobial sepsis (cecal ligation and puncture [CLP]) model in murine pregnancy and found that pregnant mice had a greater susceptibility to septic shock. In this model, mortality seemed to be associated with the development of early hemodynamic dysfunction and although circulating cytokine levels were similar, "off target" lung inflammatory cell numbers were greater in pregnant mice. Here, we have used the same CLP model to test the hypothesis that inhibiting the metabolism of the endogenous inhibitor of nitric oxide synthase, asymmetric dimethylarginine would improve the outcome of sepsis in pregnancy. We used a dimethylarginine dimethylaminohydrolase 1-selective inhibitor (L-257), which reduces vascular nitric oxide synthesis without impairing immune cell function, in combination with a broad-spectrum antibiotic (Imipenem) and studied the outcome of septic shock in pregnant mice. Treatments were administered 3 h after CLP and samples were taken 3 h later. Both Imipenem and L-257 treatment alone slightly improved mortality rates from 13% (NaCl) to 20% (Imipenem) and 33% (L-257), whereas the combination of Imipenem and L-257 significantly improved survival to 50%. Imipenem and L-257 together prevented cardiovascular collapse and improved both organ function and bacterial killing, but did not reduce lung inflammatory cell numbers and actually increased lung cytokine levels. These data suggest that conventional management in combination with selective inhibition of DDAH1 may have therapeutic potential in the management of sepsis in pregnancy. Abstract : Supplemental Digital Content is available in the text